RETRACTED: Ultrafiltration of skim milk microfiltration permeate - Mamay Dmitriy; Babenyshev Sergey; Mamay Angelina; Lisitsyn Vyacheslav (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001